2023
DOI: 10.1021/acs.jchemed.2c01001
|View full text |Cite
|
Sign up to set email alerts
|

A Refined Redox Titration Simulation Program for the Simple System

Abstract: Commonly used methods to simulate the oxidation−reduction (redox) titration curves include the three-step method and the rigorous method. The simple three-step method simulates the redox titration curve with the assumption that the reaction is complete, which is widely used in undergraduate quantitative analysis courses. For the rigorous simulation method, the concentrations of the components are obtained throughout the titration by solving the equilibrium equation, and then the potential is obtained based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…27−29 In practice there are a variety of virtual learning modules that focus on the use of software simulation for precipitation titration, 26,30 acid−base titration, 11,25,31 complexometric titration, 32,33 and redox titration. 16,34 In this study, a LabVIEW program was developed to solve equations that conform to the restrictive principles of chemical…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…27−29 In practice there are a variety of virtual learning modules that focus on the use of software simulation for precipitation titration, 26,30 acid−base titration, 11,25,31 complexometric titration, 32,33 and redox titration. 16,34 In this study, a LabVIEW program was developed to solve equations that conform to the restrictive principles of chemical…”
Section: ■ Introductionmentioning
confidence: 99%
“…Software simulation tools have gained significant popularity in the field of chemistry education. They offer a promising direction for future chemical experiment instruction, even after the COVID pandemic, which has heightened the demand for digital tools for chemical experiment teaching. , Software simulation can be utilized as simulation-based experiment courses or as supplementary training prior to conducting a specific experiment. , Such training has a lot of positive values for students to conduct experiments in real scenarios. In practice there are a variety of virtual learning modules that focus on the use of software simulation for precipitation titration, , acid–base titration, ,, complexometric titration, , and redox titration. , …”
Section: Introductionmentioning
confidence: 99%
“…16,17,26,28−34 Given that redox titrations are slightly more complicated, simulating intricate redox titration curves can be quite challenging and laborious. 16,17 The threestep method proves advantageous in the simulation of complicated redox titrations as it eliminates the need for intricate calculations, assuming the reaction is complete. However, it is important to note that this method is only applicable to systems with complete reactions, limiting its suitability in other scenarios.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The common redox titration methods generally belong to complicated redox titration situations where n 1 and n 2 are not equal to 1, such as the potassium permanganate method and the potassium dichromate method. Furthermore, slight modifications in the number of electrons gained or lost can introduce increased complexity to the Nernst equation. Regrettably, students often study this equation at a superficial level, which may limit their understanding of its intricacies and implications.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous educational publications have illustrated the value of incorporating real-world sample analysis to bridge the gap between theoretical concepts and students’ everyday experiences. Furthermore, several applications of the titration techniques to real-world samples have been published in this Journal. , These works showed that engaging in meaningful tasks that mimic real-world situations faced by experts in their respective fields allowed students a greater comprehension and integration of theoretical and experimental concepts.…”
mentioning
confidence: 99%